CENTRALIZAÇÃO E INTEGRAÇÃO NA EXPERIÊNCIA IMPERIALISTA ROMANA: UMA REFLEXÃO - Mendes, Norma Musco (Mauad X, 2020)
This article's aims to study the integration and the centralization of the Roman imperial experience by the application of two models: the model of centre and periphery and the model of the Roman economy constructed by K. Hopkins and to exemplify it with the conclusions already obtained bv my investigation about Lusitania.